Sex Differences in the Role of Neurexin 3α in Zoster Associated Pain - Kramer, Phillip R.; Umorin, Mikhail; Hornung, Rebecca; Benson, M. Douglas; Kinchington, Paul R. (Frontiers in Integrative Neuroscience, 2022)
Varicella zoster virus (VZV) induces orofacial pain and female rats show greater pain than male rats. During the proestrus phase of the estrous cycle the VZV induce pain response is attenuated in female rats. A screen of gene expression changes in diestrus and proestrus female rats indicated neurexin 3α (Nrxn3α) was elevated in the central amygdala of proestrus rats vs. diestrus rats. GABAergic neurons descend from the central amygdala to the lateral parabrachial region and Nrxn3α is important for presynaptic γ-Aminobutyric acid (GABA) release. Thus, we hypothesized that the reduced orofacial pain in male rats and proestrus female rats is the result of increased Nrxn3α within the central amygdala that increases GABA release from axon terminals within the parabrachial and inhibits ascending pain signals. To test this hypothesis Nrxn3 α expression was knocked-down by infusing shRNA constructs in the central amygdala. Then GABA release in the parabrachial was quantitated concomitant with measuring the pain response. Results revealed that knockdown of Nrxn3α expression significantly increases the pain response in both male rats and proestrus female rats vs. diestrus rats. GABA release was significantly reduced in the parabrachial of male and proestrus female rats after Nrxn3α knockdown. Neuronal activity of excitatory neurons was significantly inhibited in the parabrachial after Nrxn3α knockdown. These results are consistent with the idea that Nrxn3 within the central amygdala controls VZV associated pain by regulating GABA release in the lateral parabrachial that then modulates ascending orofacial pain signals.